The raid join the vikings - Varberg, Jeanette 1978- (Strandberg Publishing, 2021)
'The Raid - Join the Vikings' contains 16 fascinating accounts of Viking exploits during the early Viking Age. Here you can read about the Viking chieftain Ragnar's raid on Paris, Björn Ironside's expedition to the Mediterranean and the Great Heathen Army's ravaging of England. You can also read about Viking sailmaking and shipbuilding, the construction of Viking fortresses, the impact of migration and how pre-Christian beliefs mixed with the Christian religion. Scientific DNA analysis and research into the development of the written language give us close insight into the Vikings' everyday life and travels in a world of trade and royal families, weapons and slave-trading, silver coins and gold hoards. The book is written by some of the leading scientists in their respective fields, who share some of the latest research into the Viking Age. It is edited by museum curator and writer Jeanette Varberg and museum curator Peter Pentz, with a preface by Rane Willerslev, museum director.
Angekündigt auch mit dem abweichenden Titel "Setting sail"
Keywords: Geschichte 800-1050; Wikinger; Skandinavien; Ausstellungskatalog -- National Museum of Denmark -- Kopenhagen